(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: The study aimed to evaluate the efficacy of AgNORs on FNAC smears of breast lesion. Methods: FNAC were done in 200 female patients of breast lump consecutively, Papanicolau and AgNOR staining was done in all 200 cases of FNA smears.Among them biopsy and histopathology were done in 99 cases. The findings of FNAC and AgNOR analysis were compared to histopathological findings. Results: By FNAC, 53 (26.5%) cases were non-neoplastic benign, 89(44.5%) cases were benign neoplasm, 07 (3.5%) cases were atypical ductal hyperplasia and 51(25.5%) cases were malignant (Duct cell carcinoma).Among them histopathology was done in 99 cases.Out of 40 FNAC malignant cases, histopathologically all were proved malignant. Out of 42 benign cases, 1 was found malignant. 4 atypical ductal hyperplasia were also diagnosed as malignant histopathologically. True positive cases are 40, True negative cases are 36, false positive are nil (0), and false negative is 01. The sensitivity is 97.56%, specificity is 100%, positive predictive value is 100%, Negative predictive value is 97.3%, and accuracy is 98.7%. AgNOR impression were analysed in 99 histopathologically confirmed cases. The results showed benign impression in 50 cases and malignant impression in 48 cases. 01 histopathologically malignant case was impressed as benign by AgNOR and 01 as suspicious which may be included as malignant by AgNOR impression. 2 histopathologically benign cases showed higher proliferative activities and counted as malignant. True positive cases are 46, True negative 49, false positive is 02 and false negative is 01. The sensitivity is 97.87%, Specificity 96.07%, PPV 95.83%, NPV 98%, Overall accuracy is 96.93%. Conclusion: The efficacy of FNAC and AgNOR analysis in the diagnosis of breast lesion was found more or less similar and mild over lapping. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 14-20